Study on the two-dimensional micro-scale crystal growth of a coal slag. (1st October 2017) - Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Dai, Zhenghua; Liu, Haifeng
Highlights: Two-dimensional micro-scale crystal growth of a coal slag was analyzed. Crystal type and amount varied with cooling rate and isothermal temperature. High supercooling degree benefitted crystal growth during continuous cooling. Crystal growth rate first increased and then decreased during isothermal process. Abstract: The crystallization behavior of coal slag is of importance in determining slag viscosity and flow characteristics in the entrained flow gasifier. Crystal growth in the molten coal slag with the effects of cooling rate and isothermal temperature was studied based on the crystal growth and diffusion theory. Results showed that lower cooling rate promoted the crystal growth, especially in the length direction. For the cuboid crystal, the nucleation rate decreased while the length-width ratio of crystal growth increased with decreasing cooling rate at a continuous cooling rate and when held isothermally. However, under the same conditions the nucleation rate and length-width ratio of the acicular crystal increased with the decrease of cooling rate. The crystal growth rate showed an approximate linear increase in length and width direction during continuous cooling, owing to the degree of increasing supercooling. Under the isothermal condition, growth rates for the two types of crystals first increased and then decreased with the limitation of ionic diffusion and relaxation.